The Research Effect Of Chewing Function Nursing Techniques In Improving Swallowing Dysfunction Among Children With Cerebral Palsy - Liu, Ying; Zhao, Jing; Sun, Guang; Yan, Shidi; Ma, Cheng (Pacific International Journal, 2024)
The objective of this study was to analyze the efficacy of chewing function nursing techniques in improving swallowing dysfunction among children with cerebral palsy. A total of 60 children with cerebral palsy and swallowing disorders, admitted to our hospital from January 2020 to December 2022, were included in the study. The children were randomly divided into an observation group and a control group using a random number table. The control group received routine rehabilitation nursing, while the observation group received additional nursing measures focusing on chewing function techniques in addition to the routine rehabilitation nursing. Both groups underwent interventions for a period of 3 months. Swallowing dysfunction, eating ability, and oral motor function were evaluated and compared between the two groups before and after treatment. Specifically, the Dysphagia Diet Scale (DDS) was used to assess swallowing dysfunction, the Eating and Drinking Ability Classification System (EDACS) was used to evaluate eating ability, and the Structured Oral Motor Assessment (SOMA) was used to assess oral motor function. The results showed that before rehabilitation nursing, there was no significant difference in DDS scores between the two groups. However, after rehabilitation nursing, both groups exhibited lower DDS scores compared to before, and the observation group had lower scores than the control group, indicating a significant difference (P < 0.05). Similarly, before rehabilitation nursing, there was no significant difference in EDACS ratings between the two groups. After rehabilitation nursing, both groups of children showed improvement in EDACS ratings, with the observation group demonstrating better outcomes than the control group. The difference between the two groups was significant (P < 0.05). Prior to rehabilitation nursing, there was no significant difference in SOMA scores between the two groups (P > 0.05). However, after rehabilitation nursing, both groups exhibited improved SOMA scores, with the observation group scoring higher than the control group. The difference between the two groups was also significant (P < 0.05). In conclusion, compared to routine nursing care, chewing function nursing techniques can alleviate swallowing dysfunction among children with cerebral palsy, enhance their swallowing function, and improve their quality of life. Therefore, this approach is worthy of clinical application and promotion.